Synthesis and characterization of platinum doped titania and silver doped titania for photo-catalytic degradation of pre-treated palm oil mill effluent - Mohd Rizauddin, Deraman (2015)
In this study, the potential of application of photo-catalytic degradation of palm oil mill efﬂuent (POME) using metal-doped TiO2 was explored. The study comprised of synthesis and characterization of TiO2 based photo-catalysts doped with platinum (Pt) and silver (Ag) to widen the light absorption spectrum. The aim was to study the effect of photo-catalytic degradation of the pre-treated POME. The experiment was carried out under the UV and visible light and monitoring the COD degradation of pre-treated POME. Various factors affecting the photo-catalytic performance such as metal loadings and photo-catalyst loading were investigated to determine the best operating conditions for POME treatment. Physicochemical characterization studies showed that both Pt/TiO2 and Ag/TiO; have mesopores structure with BJH pore diameter ranged from 11.0 to 20.0 nm. Moreover, the catalysts possessed low BET speciﬁc surface area (7.0 to 12.0 m2/g) with the surface morphology also captured by the FESEM images. XRD diffractogram proved that the high temperature did not alter the crystalline structure of catalysts as well as the phase which was retained in anatase phase. The absorption of spectrum in visible range by Ag/TiO2 was conﬁrmed by UV-vis DRS. Results have shown that, for metal loading effects employing a minimum 0.2 g/L of photocatalyst, it can be concluded that the 0.50 wt% Pt and 0.50 wt% Ag loadings yielded the best performance with the highest apparent speciﬁc reaction rate, k,,,,,,, obtained from the ﬁrst-order Power law modelling under the irradiation of UV and visible light, respectively. In addition, the studies pertaining to the effects of photocatalyst loadings over the 0.50 wt% Pt/TiO2 and 0.50 Wt% Ag/TiO; photocatalysts showed that l.O g/L of Pt/TiO; was the optimum loading whilst for the Ag/TiO2, optimum loading was at 1.5 g/L. The photo-catalytic degradation process using both platinum doped titania and silver doped titania is the ideal solution for pome treatment. This ﬁnding should be useful in design, operation, optimization and control of photo-catalytic degradation process. For future works, other types of visible-light responsive catalysts can be employed with some in-situ activity characterizations using sophisticated equipment with various process temperatures